If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -812 = -7(12x + 8) Reorder the terms: -812 = -7(8 + 12x) -812 = (8 * -7 + 12x * -7) -812 = (-56 + -84x) Solving -812 = -56 + -84x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '84x' to each side of the equation. -812 + 84x = -56 + -84x + 84x Combine like terms: -84x + 84x = 0 -812 + 84x = -56 + 0 -812 + 84x = -56 Add '812' to each side of the equation. -812 + 812 + 84x = -56 + 812 Combine like terms: -812 + 812 = 0 0 + 84x = -56 + 812 84x = -56 + 812 Combine like terms: -56 + 812 = 756 84x = 756 Divide each side by '84'. x = 9 Simplifying x = 9
| -1+13x=341 | | -3a^2+2a+1=0 | | (-125/27)1/3 | | -16=-8(m-7)+4(7m-3) | | 29.95=62e^3x | | -3(8-7m)=30+30m | | 131-15x=-233-2x | | 3n+16=5n+2 | | 9(x-10)-4x=8x+27 | | (2x+32)*3=180 | | 56+23x=-97+26x | | 180=(3x+15)+(10x+9) | | 8t+4-6t=-22 | | x^3+4x^2-3x-6=0 | | 4x+2(x-8)=6x+20 | | 2r-12=30-4r | | f(x)=3sin(4x+1) | | 179=7(1-5n)-3 | | 12-3x=4(x-3)-x | | (x+44)=3x | | -8+3x=-17 | | 10x-2x=3 | | -3(-14y-58)=40 | | [2s-.2]=.3 | | 6(-2n+6)=132 | | 8(4a+6)+8=19-5a | | 7e^4x+10=2 | | 2(x+3)-x=30+4x | | 5x-2.3=-7-7.1 | | 6/13y=-1 | | 14x+6y=1292 | | 7*e^4*x+10=2 |